The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Advances in Financial Risk Management 2013
DOI: 10.1057/9781137025098_11
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Fuzzy GJR-GARCH Modeling Approach for Stock Market Volatility Forecasting

Abstract: Forecasting stock market returns volatility is a challenging task that has attracted the attention of market practitioners, regulators and academics in recent years. This paper proposes a Fuzzy GJR-GARCH model to forecast the volatility of S&P 500 and Ibovespa indexes. The model comprises both the concept of fuzzy inference systems and GJR-GARCH modeling approach in order to consider the principles of time-varying volatility, leverage effects and volatility clustering, in which changes are cataloged by similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…They used the GJR-GARCH model to estimate the extreme tail risk. Moreover, Maciel (2013) applied a similar methodology in the stock market. As cryptocurrencies suffer from fat-tail risk, we prefer to implement the GJR-GARCH model to accurately estimate the volatility of cryptocurrencies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They used the GJR-GARCH model to estimate the extreme tail risk. Moreover, Maciel (2013) applied a similar methodology in the stock market. As cryptocurrencies suffer from fat-tail risk, we prefer to implement the GJR-GARCH model to accurately estimate the volatility of cryptocurrencies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors concluded that those forecasts obtained from GK-ARMA models are in general as good as those obtained from more complex GARCH models. More examples of previous literature in Brazil are Santanda and Bueno 2008, Woo et al (2009), Mendes and Accioly (2012), Maciel (2012), and Vicente et al (2012).…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…e hybrid fuzzy time series models proposed in references [10,11] have shown important enhancements in forecasting stock market volatility, outperforming the traditional time series models, neural networks, other hybrid models, etc. Adaptive neurofuzzy information system (ANFIS) is a different popular hybrid model used in volatility forecasting [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%